PENINGKATAN HASIL BELAJAR PKn MELALUI MODEL PEMBELAJARAN SCRAMBLE - Samsul Huda (MEDIA DIDAKTIKA, 2021)
This study aims to improve civics learning outcomes (Citizenship Education) by using scramble learning models for fifth grade students of the German Elementary School in Sugio Subdistrict, Lamongan Regency. This type of research is classroom action research. The research subjects were fifth grade students of SD Negeri German Sugio Subdistrict, Lamongan Regency, amounting to 17 students. The method of data collection in the research is in the form of tests, observations, and documentation. The research instruments were in the form of tests and learning implementation sheets. The data analysis technique used is descriptive quantitative and qualitative. The results showed an increase in PKn learning outcomes of fifth grade students of SD Negeri German Sugio Subdistrict Lamongan Regency after using the scramble learning model in cycle I and cycle II. Based on the results of tests in the implementation of learning with scramble learning models, students who achieved a value of ≥75 were 70.59% in the first cycle and increased to 88.24% in the second cycle.